Ancestralidade e memória nas escrevivências de Carolina Maria de Jesus e Conceição Evaristo: o elo entre passado e presente nas narrativas - Paim, Luciane de Lima (2023)
Carolina Maria de Jesus and Conceição Evaristo are the voices of their ancestors; they are the written and spoken representations of a people who have always had their history, their experiences, their trajectories, and their cultures made invisible, due to the predominance of the Western and Eurocentric paradigms in the narratives. On one hand, we have Carolina, with all her experience, the wisdom of life, courage, and audacity, explaining her experiences in the face of a discriminatory and racist society. On the other, we have Conceição, with her experiences in writing, a listener, as she mentions in her speeches, a woman who rose from the moment she chose to give new meaning to words, and decided to continue the path started by Carolina: to give voice to those who are reduced to the eviction room. To be able to explain the experiences of black people, both authors resort to mechanisms such as memories and written and spoken records, of their own or others, to tell the discrimination, prejudice, pain, violence, and authoritarianism that these people faced. Thus, the objective of this research is to identify which are the places of memory and how much ancestry is present in the construction of the narratives Quarto de despejo: diário de uma favelada, by Carolina Maria de Jesus, and Becos da Memória, by Conceição Evaristo. Furthermore, we intend to identify how the link between the past and the present can re-signify the history of Afro-Brazilian people, based on the exhibitions carried out through the memories of the author/narrators. Furthermore, we aim to establish relationships between the works, even though one is an autobiography and the other is fiction since much has already been written about Conceição basing herself on Carolina's trajectories to write her narratives and about having Carolina as a source of inspiration in life and writing. Methodologically, we start from the bibliographical research and, in the sequence, we analyze excerpts from the narratives that identify the places of memory and how these influenced the representation of the past and the present within the selected corpus. Nevertheless, this thesis intends to demonstrate how Black Literature of female authorship relates to a legacy of black people, through the "writings" of two black women, who broke the barrier of the predetermined and establish in their writings the intersectional dialogue to talk about gender, race and class, such important themes in contemporary Brazil.